Characterization of quorum sensing genes and N-acyl homoserine lactones in Citrobacter amalonaticus strain YG6 - Kher, Heng Leong; Krishnan, Thiba; Letchumanan, Vengadesh; Hong, Kar Wai; How, Kah Yan; Lee, Learn Han; Tee, Kok Keng; Yin, Wai Fong; Chan, Kok Gan (Elsevier, 2019)
In the phylum of Proteobacteria, quorum sensing (QS) system is widely driven by synthesis and response of N-acyl homoserine lactone (AHL) signalling molecules. AHL is synthesized by LuxI homologue and sensed by LuxR homologue. Once the AHL concentration achieves a threshold level, it triggers the regulation of target genes. In this study, QS activity of Citrobacter amalonaticus strain YG6 which was isolated from clams was investigated. In order to characterise luxI/R homologues, the genome of C. amalonaticus strain YG6 (4.95 Mbp in size) was sequenced using Illumina MiSeq sequencer. Through in silico analysis, a pair of canonical luxI/R homologues and an orphan luxR homologue were identified and designated as camI, camR, and camR2, respectively. A putative lux box was identified at the upstream of camI. The camI gene was cloned and overexpressed in E. coli BL21 (DE3)pLysS. High-resolution triple quadrupole liquid chromatography mass spectrometry (LC-MS/MS) analysis verified that the CamI is a functional AHL synthase which produced multiple AHL species, namely N‑butyryl‑L‑homoserine lactone (C4-HSL), N‑hexanoyl‑L‑homoserine lactone (C6-HSL), N‑octanoyl‑L‑homoserine lactone (C8-HSL), N‑tetradecanoyl‑L‑homoserine lactone (C14-HSL) and N‑hexadecanoyl‑L‑homoserine lactone (C16-HSL) in C. amalonaticus strain YG6 and camI gene in recombinant E. coli BL21(DE3)pLysS. To our best knowledge, this is the first functional study report of camI as well as the first report describing the production of C14-HSL by C. amalonaticus.